PENGENALAN DASAR MIKROTIK SISWA/I TKJ SMK YADIKA 5 - Agung Wijoyo; Indra Cahya Firdaus; Sofyan Mufti Prasetiyo (CV. Multi Kreasi Media, 2023)
Information technology is growing rapidly, especially in the social and organizational fields. This can be seen from the good use of the internet by the community in order to explore broader knowledge. The impact of this is that the teacher is no longer the only source of learning knowledge. One of the roles of Information Technology in society is to produce various types of learning media, namely interactive learning media. This learning media contains learning materials that are equipped with various content that helps in conveying learning content. The content is in the form of images, illustrations, sounds, videos, or interactive animations. Several studies that have been conducted show that interactive learning media based on Information Technology can be used as the main reference in the learning process because it is more flexible, effective, and efficient. This information must be interpreted properly by the public so that there is no misinformation in the delivery of information to the public. By utilizing Information Technology, these communication symbols can be made in the form of images, illustrations, or animations. The symbols created are packaged in an interactive learning media. With interactive learning media, conceptual errors in learning can be minimized. Based on the demands of the 2013 curriculum, the learning process must use a scientific approach, so the interactive learning media developed must also contain that approach. The scientific approach in question is containing the steps of observing, asking, associating, trying, and communicating. The scientific approach is applied to maintain scientific values in the community so that their scientific attitude continues to develop.